Socioeconomic diversity and typology of Bedouin communities in the hot dry Coastal Zone of Western Desert, Egypt - Adel M. Aboul-Naga; Waheed Mogahed; Faten Fahmy; Mohamed Elshafi; Ehab S. Abdel-Aal; Tarek Abdel-khalek; Taha H. Abdelsabour; Veronique Alary; Veronique Alary (Frontiers in Sustainable Food Systems, 2022)
The study was carried out to assess the diversity of the farming system and the associated development needs of Bedouin communities in the rural area of the hot dry Coastal Zone of Western Desert (CZWD), Egypt with the objective of improving surveillance of the Bedouin communities to the harsh desert conditions. The area has low irritated rainfall (60–140 mm/yr.) and frequent incidences of drought. Specially designed questionnaires were adopted on 151 householders and 51 women groups in 4 locations. More than 50% of the householders are fully engaged in agriculture activities, whereas 31% of them are partially engaged in other businesses. The householders are extended families of 12.2 members on average. Gender differences in education are recognizable; 20% of boys ≥15 years of age are illiterate vs. 60% of girls. Dominant agricultural activities of the householders are sheep raising (98.7%), goat raising (89.4%), olive and figs cultivation (84%), and rain-fed barley (78%). Land tenure averages 31.3 acres/ household. Crop cultivation relies on rainfall, 29% of the householders apply supplement irrigation for fruit trees and vegetables. Natural pasture is an important asset for livestock, where small householders do not hold pastureland. Females do not contribute to field cropping, while 53% of them participate in animal husbandry, especially at the house. The typology of the studied stakeholders showed clear diversification in farming systems. They are clustered into four groups; depending mainly on the livestock assets, followed by the land/crop and human assets. Number of species and flock size are the most important variables for the diversity of stakeholders. The cultivated area is the main variable within land/crop assets, family members in livestock and family size are the main variables from human assets. Most of the householders (95%) give their top need for water cisterns, water reservoirs ranked second (78.6%), followed by raising and improving goats. Pasture development got the lowest priority. Goat and poultry rearing, followed by dairy processing got the top needs of women.